Cost and effectiveness analysis of immunization service delivery support in Andhra Pradesh, India - Chutima Suraratdecha; CBS Venkata Ramana; Satish Kaipilyawar; JVG Krishnamurthy; Srilatha Sivalenka; Naveena Ambatipudi; Sanjay Gandhi; K Umashankar; James Cheyne
The immunization service delivery support (ISDS) model was initiated in Andhra Pradesh, India, in November 2003 with the aim of strengthening immunization services through supportive supervision. The ISDS model involves a well-established supervision system built upon the existing health infrastructure. The objectives of this approach are to: (1) identify areas of high performance and those that need improvement, (2) assist staff in identifying and correcting wrong practices, (3) improve staff skills, (4) motivate staff, and (5) initiate corrective actions at appropriate levels through information sharing. An evaluation of cost and effectiveness of ISDS in 16 districts that participated in the programme found that the incremental cost associated with three rounds of supportive supervision visits was approximately US$ 110 630 (US$ 36 877 per round). The performance of health centre and immunization sessions was evaluated using 43- and 28-point checklists, respectively, and demonstrated significant improvement during and following the two-year implementation of ISDS. The average percentage change in health centre performance scores from baseline to the fourth round of evaluation was approximately 36%, and immunization session performance scores increased by an average of 9%. The incremental costs per additional per cent increase in average health centre performance score and per additional per cent increase in average immunization session performance score over the evaluation period were estimated to be US$ 3091 and US$ 12 760, respectively. The incremental cost-effectiveness ratios are relatively sensitive to personnel and travel costs. Integration of ISDS into the Andhra Pradesh immunization system is projected to result in a 39% potential cost savings per round of supervision visit.